STRATEGI PERCEPATAN PROYEK MENGGUNAKAN METODE CRASH PROGRAM (Studi Kasus : Program Kerja Masa Pengeringan Proyek Rehabilitasi Saluran Induk Klambu Kiri Tahun 2017) - Eko Marsudi Utomo; Mochamad Agung Wibowo; Sriyana Sriyana (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
Based on the initial plan from the contract of the Rehabilitation Klambu Kiri’s Project, main channel's work was carried out continously by an open and closed system using the kistdam method. However by the time of execution work, the stakeholders wanted the work in the main channel to be carried out based on cropping pattern, where there a drying period and a drainage period. In this case, flow area and bottom structure of the channel can only be worked during the drying period lasting three months. To be able to determine the impact of these change, a duration calculation is carried out from project's data which are internal's BQ, initial plan's resources, and the relations between activities using Microsoft Project on the flow section structure which be worked in drying period of 2017. The normal duration obtained from analysis is 203 days. It was exceeded time of drying period and possibly could have an impact on the overall project completion schedule resulting in delays, defaults and even termination of contracts. Therefore, it is necessary to have an accelerate strategy of the work on the flow section structure to be completed within a predetermined time. In this study, the acceleration strategy was carried out using crashing analysis in the critical activities from normal duration using Microsoft Project. The crashing method was carried out in stages from the crashing simulation of 30 days, 60 days, to 120 days so that obtained the duration of acceleration was 83 days. The cost component of acceleration is calculated by choosing the lowest cost from the alternatives of increasing work hours (overtime) or by adding resources. From the simulation results, the crash cost to complete the acceleration work is Rp. 1.298.307.591,- or about 2,05% of direct cost, so the efficiency is Rp. 9.692.409,- from normal duration